Obesity Increases Risk‐Adjusted Morbidity, Mortality, and Cost Following Cardiac Surgery. Issue 3 (8th March 2017) - Ghanta, Ravi K.; LaPar, Damien J.; Zhang, Qianzi; Devarkonda, Vishal; Isbell, James M.; Yarboro, Leora T.; Kern, John A.; Kron, Irving L.; Speir, Alan M.; Fonner, Clifford E.; Ailawadi, Gorav
Abstract : Background: Despite the epidemic rise in obesity, few studies have evaluated the effect of obesity on cost following cardiac surgery. We hypothesized that increasing body mass index (BMI) is associated with worse risk‐adjusted outcomes and higher cost. Methods and Results: Medical records for 13 637 consecutive patients who underwent coronary artery bypass grafting (9702), aortic (1535) or mitral (837) valve surgery, and combined valve–coronary artery bypass grafting (1663) procedures were extracted from a regional Society of Thoracic Surgeons certified database. Patients were stratified by BMI: normal to overweight (BMI 18.5–30), obese (BMI 30–40), and morbidly obese (BMI >40). Differences in outcomes and cost were compared between BMI strata and also modeled as a continuous function of BMI with adjustment for preoperative risk using Society of Thoracic Surgeons predictive risk indices. Morbidly obese patients incurred nearly 60% greater observed mortality than normal weight patients. Moreover, morbidly obese patients had greater than 2‐fold increase in renal failure and 6.5‐fold increase in deep sternal wound infection. After risk adjustment, a significant association was found between BMI and mortality ( P <0.001) and major morbidity ( P <0.001). The risk‐adjusted odds ratio for mortality for morbidly obese patients was 1.57 ( P =0.02) compared to normal patients. Importantly, risk‐adjusted total hospital cost increased with BMI, with 17.2% higher costs in morbidly obese patients. Conclusions: Higher BMI is associated with increased mortality, major morbidity, and cost for hospital care. As such, BMI should be more strongly considered in risk assessment and resource allocation.